Download presentation
Presentation is loading. Please wait.
1
Given: h(x) = 6 x2 - x – 10 find h(-3)
You must square first. This is called evaluating using DIRECT SUBSTITUTION.
2
Given: h(x) = 6 x2 - x – 10 find h(-3)
We can also evaluate a function using SYNTHETIC SUBSTITUTION. Given: h(x) = 6 x2 - x – 10 find h(-3) Step 1: We need the coefficients: 6, -1, -10 Step 2: -18 57 Solution 6 -19 47 Step 3: Bring down the 6. Multiply it by -3 and then add it to the – 1.
3
Given: h(x) = 4 x3 - x – 10 find h(2)
Step 1: We need the coefficients: 4, 0, -1, -10 Step 2: 8 16 30 4 8 15 20 Given: h(x) = 4 x4 - x2 – 10 We’d have to replace all the “missing” x’s with zeros… h(x) = 4x4 + 0x3 – x2 + 0x - 10
4
How could you find it’s x intercepts?
Consider: h(x) = - x2 - x + 10 What’s it’s y intercept? Does it flip up or down? What does it graph? Vertex? How could you find it’s x intercepts?
5
Consider: h(x) = - x2 - x + 10 It’s called an EVEN function because it is of degree: 2 It’s flips down because the leading coefficient is -1
6
Consider: h(x) = 3x2 - x + 10 It’s called an EVEN function because it is of degree: 2 It’s flips UP because the leading coefficient is 3
7
Consider: h(x) = - x3 - x + 10 It’s called an ODD function because it is of degree: 3 It’s flips down because the leading coefficient is -1
8
Consider: h(x) = 2x3 - x + 10 It’s called an ODD function because it is of degree: 3 It’s flips UP because the leading coefficient is 2
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.